A study on incidence and severity of acute renal failure and its association with parasite density in hospitalised patients with falciparum malaria - Pinaki Mukhopadhyay; Biman Kumar Das; NM Biswas (International Journal of Medical Research and Review, 2017)
Aims of the study: To find out the incidence of acute renal failure in falciparum malaria and to correlate between the degree of parasitism at presentation with acute renal failure and its outcome in falciparum malaria.Methodology: Each patient with a history of fever, suggestive of severe malaria was subjected to peripheral blood smear examinations, up to 3 samples were examined or till positive and/or Pf antigen positive cases. The selected patients were then grouped according to the clinical features, laboratory parameters and were followed up for the outcome.Results: Out of the 50 cases of acute renal failure due to falciparum malaria, 21 had Parasite density <5% (42%), 13 had 5-10%(26%) and 16 had >10%(32%). Out of 21 cases of mild ARF 12 patients had parasite density<5% and 9 had >5%. Out of 29 cases of severe ARF 9 patients had parasite density<5% and 20 had >5%. Dialysis was done in a total of 31 cases (62%). In the severe form of acute renal failure. hemodialysis was required in 29 cases (58%), in the milder form of renal failure; only 2 cases (4%) required hemodialysis. Rests of the cases were managed by conservative treatment.Conclusion: Parasite Density has significant impact to predict the severity of renal failure, duration of hospital stays as well as the number of dialysis required. As the study was conducted with small number of cases, further study is necessary with large number of cases to arrive at a conclusion regarding the malady of acute renal failure in falciparum malaria.